A kind of water-based inorganic coating and preparation method thereof
By modifying the potassium silicate solution and adding appropriate fillers and polymer emulsions, the problem of insufficient stability of silicate-based water-based inorganic coatings during storage is solved, and the coating is highly water-resistant, impact-resistant and good storage is achieved. stability.
Patent Information
- Application Number
- CN202411615540.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing silicate-based aqueous inorganic coatings have stability problems such as water separation, coarse retraction and thickening during storage, which affects the performance of the use.
Modified potassium silicate solution is used, and modified by mixing with a silica sol and using a silane coupling agent to improve the modulus and stability of the potassium silicate solution, while adding heavy calcium carbonate, feldspar powder, titanium dioxide and polymer. lotion, optimize the composition of the coating.
It extends the shelf life of the coating, improves the water resistance, impact resistance and storage stability of the coating, and ensures the construction and spraying performance of the coating.
Smart Images

Figure RNE1RB4DH62VZPOFEO1KP9JIOVCXJBTI847LVQP8
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coatings, and more specifically, to a water-based inorganic coating and a preparation method thereof. Background Art
[0002] Waterborne inorganic coatings refer to environmentally friendly coatings with inorganic materials as the main film-forming substances. Due to their excellent environmental performance and physical and chemical properties, such as non-toxicity, odorlessness, non-irritation, and excellent fire resistance, mildew resistance, acid and alkali resistance, they are widely used in many fields such as construction, furniture, and automobiles. According to the different inorganic materials, waterborne inorganic coatings can be mainly divided into silicate-based waterborne inorganic coatings, silica sol-based waterborne inorganic coatings, and phosphate-based waterborne inorganic coatings. Among them, silicate-based waterborne inorganic coatings are the most commonly used in the construction field.
[0003] The prior art discloses a silicate-based water-based inorganic coating, which includes the following components in mass ratio: 20-25% potassium silicate solution, 22.5-27.5% calcium carbonate, 7.5-12.5% titanium dioxide, 3-6% kaolin, 0.1-0.2% defoamer, 0.3-0.6% dispersant, 0.1-0.2% wetting agent, 0-0.5% stabilizer, 2-8% styrene acrylic emulsion, and the balance is water. The coating has excellent weather resistance, fire retardancy, antibacterial and mildew resistance, is environmentally friendly, has a low content of organic volatiles, and is suitable for use as a building coating.
[0004] However, the above-mentioned silicate-based water-based inorganic coating still has the following technical defects: potassium silicate solution has both solution and colloid properties, and colloid particles will continue to grow during storage, affecting the performance of the coating. Even if stabilizers are added, the storage stability of the above-mentioned coating is still insufficient, and it is easy to cause water separation, coarsening and severe thickening. Summary of the invention
[0005] In order to improve the storage stability of the coating, the present application provides a water-based inorganic coating and a preparation method thereof.
[0006] In the first aspect, the present application provides a water-based inorganic coating, which adopts the following technical solution:
[0007] A water-based inorganic coating comprises the following components in parts by weight:
[0008] 18-24 parts of modified potassium silicate solution;
[0009] Heavy calcium carbonate 22-30 parts;
[0010] 4-6 parts of feldspar powder;
[0011] 8-13 parts of titanium dioxide;
[0012] 3-6 parts of polymer emulsion;
[0013] Defoaming agent 0.1-0.2 parts;
[0014] Dispersant 0.2-0.5 parts;
[0015] 20-30 parts water;
[0016] The preparation process of the modified potassium silicate solution is as follows:
[0017] The first step is to mix 3-5 parts of silane coupling agent, 0.1-0.2 parts of acetic acid and 10-15 parts of water by weight, heat to 50-60° C., and react for 30-60 minutes to obtain a coupling agent solution;
[0018] In the second step, 40-50 parts of low modulus potassium silicate solution and 15-20 parts of silica sol are mixed, stirred continuously and heated to 55-60°C, kept warm for 40-60 minutes, 2-3 parts of coupling agent solution and 15-20 parts of water are added, kept warm for 2-3 hours, cooled to room temperature, and the modified potassium silicate solution is obtained.
[0019] By adopting the above technical solution, the modulus of the potassium silicate solution refers to the molar ratio of silicon dioxide and potassium oxide in the solution, which has an important influence on various performances of the coating. After the low modulus potassium silicate solution is mixed with silica sol, the silicon dioxide particles react with the silanol groups to increase the modulus. As the modulus of the potassium silicate solution increases, the hardness and density of the coating increase, and the wear resistance and water resistance are improved, but the brittleness of the coating increases, the impact resistance decreases, and the storage stability decreases due to excessive active silanol groups. The coupling agent can modify the potassium silicate solution, inhibit the reactivity of the reaction system, thereby extending the storage period of the coating and improving the water resistance of the coating.
[0020] Heavy calcium carbonate, feldspar powder and titanium dioxide are compounded as fillers. Heavy calcium carbonate is used as a system pigment, which has a filling effect, can make the coating delicate and uniform, and improve whiteness. Heavy calcium carbonate also has a certain dry hiding power, especially when using ultra-fine products, it can improve the hiding effect of titanium dioxide. Feldspar powder is composed of angular nodular particles, which can form a denser coating film, give the coating film high wear resistance and scratch resistance, and improve the anti-corrosion performance of the coating film. Titanium dioxide is a high-quality white inorganic pigment with high whiteness and strong hiding power, which can improve the opacity of the coating and the firmness of the coating film.
[0021] Polymer emulsions can improve the stability of inorganic coatings, making the coatings perform better during storage and construction. By adjusting the rheological properties of the coating, polymer emulsions help improve the coating's workability and spraying performance. Polymer emulsions can significantly improve the coating's scrub resistance and water resistance, especially the early resistance to dry and wet rub-off and water resistance. In addition, since the coating film formed after the inorganic coating is cured is relatively rigid, adding polymer emulsions can increase the flexibility of the coating film and reduce the risk of cracking and shedding due to temperature changes or other external factors.
[0022] Optionally, the low modulus potassium silicate solution has a modulus of 2-2.5 and a mass concentration of 30-35 wt %.
[0023] By adopting the above technical scheme, the potassium silicate solution with this modulus has good fluidity, which is convenient for preparing the modified potassium silicate solution and ensures that the prepared modified potassium silicate solution has appropriate modulus and moderate performance, and the coating has excellent wear resistance, storage stability and impact resistance.
[0024] Optionally, the preparation process of the silane coupling agent is as follows: by weight, 10-13 parts of γ-glycidyloxypropyltrimethoxysilane, 15-17 parts of benzotriazole and 0.2-0.4 parts of Fe3O4 are mixed evenly, the temperature is raised to 120-130°C, the reaction is carried out for 45-60 minutes, the temperature is lowered and the material is discharged to obtain the silane coupling agent.
[0025] By adopting the above technical scheme, γ-glycidyloxypropyltrimethoxysilane and benzotriazole undergo a ring-opening reaction to generate a silane coupling agent with a benzotriazole group. Benzotriazole is a highly efficient copper corrosion inhibitor that can form a stable chemical bond with the metal, thereby improving the water resistance of the coating. A composite film can be formed on the metal surface in a strong acid, weak acid, neutral and weak alkaline environment, effectively preventing the penetration of water molecules and the erosion of corrosive ions. The silane coupling agent modified by benzotriazole can increase the stability of the potassium silicate solution, reduce its sedimentation and stratification during storage, and make the modified potassium silicate solution have better chemical stability, thereby improving the storage stability of the coating. Due to the ability of benzotriazole to form a chelate with the metal, the modified potassium silicate solution can enhance the adhesion between the coating and the metal substrate, increase the toughness of the coating, thereby improving the impact resistance of the coating, making the coating less likely to break or fall off when impacted.
[0026] Optionally, in the first step of the preparation process of the modified potassium silicate solution, 0.1-0.2 parts by weight of phytic acid is also added.
[0027] By adopting the above technical scheme, the addition of phytic acid can improve the modification effect of benzotriazole on the silane coupling agent, so that after the potassium silicate solution is modified, the water resistance, impact resistance and storage stability of the coating are improved.
[0028] Optionally, 2-3 parts of hemp oil are also included by weight.
[0029] By adopting the above technical solution, hemp oil can be soluble in water, suitable for water-based paint systems, and can improve the storage stability of the paint, especially the low-temperature stability.
[0030] Optionally, the preparation process of the polymer emulsion is as follows:
[0031] The first step is to mix 20-25 parts of triethoxyvinylsilane, 0.6-0.9 parts of p-toluenesulfonic acid and 150-200 parts of tetrahydrofuran by weight under nitrogen protection, continue stirring and heat to 65-70° C., then add 30-40 parts of 4-fluoro-1-butanol, react for 3-5 hours, cool, filter, and distill under reduced pressure to obtain a fluorosilicone monomer;
[0032] The second step is to mix 60-70 parts of butyl acrylate, 1.5-2 parts of OP-10, 0.3-0.5 parts of sodium bicarbonate and 300-400 parts of water under nitrogen protection, stir for 20-30 minutes, add 0.02-0.03 parts of potassium persulfate, heat to 80-85°C, react for 60-80 minutes, and obtain butyl acrylate emulsion;
[0033] The third step is to mix the above fluorosilicone monomer with 20-30 parts of butyl acrylate, 40-50 parts of methyl methacrylate, 1.5-2 parts of OP-10, 0.3-0.5 parts of potassium persulfate and 500-600 parts of water, stir for 20-30 minutes, then add the above butyl acrylate emulsion, heat to 70-80°C, react for 3-4 hours and then discharge to obtain a polymer emulsion.
[0034] By adopting the above technical solution, the polymer emulsion is a self-made fluorinated silicone-acrylic emulsion. Compared with ordinary emulsions, the introduction of fluorine atoms makes the coating have excellent hydrophobic and oleophobic properties, which can significantly improve water resistance. In addition, the fluorine atoms and the modified potassium silicate solution can be chemically bonded to improve the storage stability of the coating.
[0035] Optionally, the polymer emulsion accounts for more than 25 wt % of the mass of the modified potassium silicate solution.
[0036] By adopting the above technical solution, the fluorinated silicone-acrylic emulsion can be added in a high content compared to the ordinary silicone-acrylic emulsion to ensure the comprehensive performance of the coating.
[0037] Optionally, the defoaming agent is a polyether defoaming agent.
[0038] By adopting the above technical solution, the polyether defoamer has excellent defoaming and anti-foaming properties, can quickly eliminate foam, and prevent the regeneration of foam for a long time.
[0039] Optionally, the dispersant is a non-ionic dispersant.
[0040] By adopting the above technical solution, the non-ionic dispersant can expand rapidly, increase the contact area between water and the solid surface, reduce surface tension, and improve wettability.
[0041] In a second aspect, the present application provides a method for preparing a water-based inorganic coating, using the following technical solution:
[0042] A method for preparing a water-based inorganic coating comprises the following steps: mixing modified potassium silicate solution, heavy calcium carbonate, feldspar powder, titanium dioxide, polymer emulsion, defoamer, dispersant and water according to the required weight parts of the formula and stirring evenly to obtain the water-based inorganic coating.
[0043] In summary, this application has the following beneficial effects:
[0044] 1. The present application uses a silane coupling agent to modify the potassium silicate solution, inhibit the reactivity of the reaction system, thereby extending the storage period of the coating and improving the water resistance of the coating;
[0045] 2. In this application, silica sol is used to increase the modulus of potassium silicate solution, so that the hardness and density of the coating are improved, and the wear resistance and water resistance are improved;
[0046] 3. The silane coupling agent of the present application adopts γ-glycidyloxypropyltrimethoxysilane and benzotriazole for ring-opening reaction, has benzotriazole group, and can improve the storage stability and impact resistance of the coating. DETAILED DESCRIPTION
[0047] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0048] The examples of this application use the following raw materials:
[0049] The silica sol has a solid content of 25 wt % and an average particle size of 10 nm. The defoamer is a polyether defoamer, model PE-6800, purchased from BASF. The dispersant is a non-ionic dispersant, model PX 4701, purchased from BASF.
[0050] Preparation Example 1:
[0051] The preparation process of modified potassium silicate solution is as follows:
[0052] In the first step, 10 kg of γ-glycidyloxypropyltrimethoxysilane, 15 kg of benzotriazole and 0.2 kg of Fe3O4 were mixed evenly, heated to 120°C, reacted for 45 minutes, cooled and discharged to obtain a silane coupling agent;
[0053] In the second step, 3 kg of silane coupling agent, 0.1 kg of acetic acid and 10 kg of water were mixed evenly, heated to 50° C., and reacted for 30 minutes to obtain a coupling agent solution;
[0054] In the third step, 40 kg of low modulus potassium silicate solution and 15 kg of silica sol are mixed, stirred continuously and heated to 55°C. After keeping warm for 40 minutes, 2 kg of coupling agent solution and 15 kg of water are added, and the mixture is kept warm for 2 hours. The mixture is cooled to room temperature and the modified potassium silicate solution is obtained.
[0055] The modulus of the low modulus potassium silicate solution is 2, and the mass concentration is 30wt%.
[0056] Preparation Example 2:
[0057] The preparation process of modified potassium silicate solution is as follows:
[0058] In the first step, 13 kg of γ-glycidyloxypropyltrimethoxysilane, 17 kg of benzotriazole and 0.4 kg of Fe3O4 were mixed evenly, heated to 130°C, reacted for 60 minutes, cooled and discharged to obtain a silane coupling agent;
[0059] In the second step, 5 kg of silane coupling agent, 0.2 kg of acetic acid and 15 kg of water were mixed evenly, heated to 60° C., and reacted for 60 min to obtain a coupling agent solution;
[0060] In the third step, 50 kg of low modulus potassium silicate solution and 20 kg of silica sol are mixed, stirred continuously and heated to 60°C. After keeping warm for 60 minutes, 3 kg of coupling agent solution and 20 kg of water are added, and the mixture is kept warm for 3 hours. The mixture is cooled to room temperature and the modified potassium silicate solution is obtained.
[0061] The modulus of the low modulus potassium silicate solution is 2.5, and the mass concentration is 35wt%.
[0062] Preparation Example 3:
[0063] The preparation process of modified potassium silicate solution is as follows:
[0064] In the first step, 12 kg of γ-glycidyloxypropyltrimethoxysilane, 16 kg of benzotriazole and 0.3 kg of Fe3O4 were mixed evenly, heated to 125°C, reacted for 50 minutes, cooled and discharged to obtain a silane coupling agent;
[0065] In the second step, 4 kg of silane coupling agent, 0.15 kg of acetic acid and 12 kg of water were mixed evenly, heated to 55° C., and reacted for 45 minutes to obtain a coupling agent solution;
[0066] In the third step, 45 kg of low modulus potassium silicate solution and 18 kg of silica sol were mixed, stirred continuously and heated to 58°C. After keeping warm for 50 minutes, 2.5 kg of coupling agent solution and 18 kg of water were added, and the mixture was kept warm for 2.5 hours. The mixture was cooled to room temperature and the modified potassium silicate solution was obtained.
[0067] The modulus of the low modulus potassium silicate solution is 2.2, and the mass concentration is 32wt%.
[0068] Preparation Example 4:
[0069] The only difference from Preparation Example 3 is that the mass of the silane coupling agent is replaced by γ-glycidyloxypropyltrimethoxysilane.
[0070] Preparation Example 5:
[0071] The preparation process of polymer emulsion is as follows:
[0072] In the first step, under nitrogen protection, 20 kg of triethoxyvinylsilane, 0.6 kg of p-toluenesulfonic acid and 150 kg of tetrahydrofuran were mixed, stirred continuously and heated to 65°C, and then 30 kg of 4-fluoro-1-butanol was added. After reacting for 3 hours, the mixture was cooled, filtered and distilled under reduced pressure to obtain a fluorosilicone monomer;
[0073] In the second step, under nitrogen protection, 60 kg of butyl acrylate, 1.5 kg of OP-10, 0.5 kg of sodium bicarbonate and 300 kg of water were mixed, stirred for 20 minutes, and then 0.02 kg of potassium persulfate was added, the temperature was raised to 80° C., and the reaction was carried out for 60 minutes to obtain butyl acrylate emulsion;
[0074] In the third step, the fluorosilicone monomer is mixed with 20 kg butyl acrylate, 40 kg methyl methacrylate, 1.5 kg OP-10, 0.3 kg potassium persulfate and 500 kg water, stirred for 20 min, and then the butyl acrylate emulsion is added, the temperature is raised to 70° C., and the reaction is carried out for 3 hours before discharging the material to obtain a polymer emulsion.
[0075] Preparation Example 6:
[0076] The preparation process of polymer emulsion is as follows:
[0077] In the first step, under nitrogen protection, 25 kg of triethoxyvinylsilane, 0.9 kg of p-toluenesulfonic acid and 200 kg of tetrahydrofuran were mixed, stirred continuously and heated to 70°C, and then 40 kg of 4-fluoro-1-butanol was added. After reacting for 5 hours, the mixture was cooled, filtered and distilled under reduced pressure to obtain a fluorosilicon monomer;
[0078] In the second step, under nitrogen protection, 70 kg of butyl acrylate, 2 kg of OP-10, 0.5 kg of sodium bicarbonate and 400 kg of water were mixed, stirred for 30 minutes, and then 0.03 kg of potassium persulfate was added, the temperature was raised to 85° C., and the reaction was carried out for 80 minutes to obtain butyl acrylate emulsion;
[0079] In the third step, the fluorosilicone monomer is mixed with 30 kg butyl acrylate, 50 kg methyl methacrylate, 2 kg OP-10, 0.5 kg potassium persulfate and 600 kg water, stirred for 30 min, and then the butyl acrylate emulsion is added, the temperature is raised to 80° C., and the reaction is performed for 4 h before discharging the mixture to obtain a polymer emulsion.
[0080] Preparation Example 7:
[0081] The preparation process of polymer emulsion is as follows:
[0082] In the first step, under nitrogen protection, 22 kg of triethoxyvinylsilane, 0.8 kg of p-toluenesulfonic acid and 180 kg of tetrahydrofuran were mixed, stirred continuously and heated to 68°C, and then 35 kg of 4-fluoro-1-butanol was added. After reacting for 4 hours, the mixture was cooled, filtered and distilled under reduced pressure to obtain a fluorosilicon monomer;
[0083] In the second step, under nitrogen protection, 65 kg of butyl acrylate, 1.8 kg of OP-10, 0.4 kg of sodium bicarbonate and 350 kg of water were mixed, stirred for 25 minutes, and then 0.026 kg of potassium persulfate was added, the temperature was raised to 81° C., and the reaction was carried out for 70 minutes to obtain a butyl acrylate emulsion;
[0084] In the third step, the fluorosilicone monomer is mixed with 25 kg butyl acrylate, 45 kg methyl methacrylate, 1.8 kg OP-10, 0.4 kg potassium persulfate and 550 kg water, stirred for 25 min, and then the butyl acrylate emulsion is added, the temperature is raised to 75° C., and the reaction is carried out for 3.5 h before discharging the material to obtain a polymer emulsion.
[0085] Embodiment 1:
[0086] A water-based inorganic coating comprising the following components by weight:
[0087] 24 kg of modified potassium silicate solution, prepared in Preparation Example 1;
[0088] Heavy calcium carbonate 30kg;
[0089] Feldspar powder 6kg;
[0090] Titanium dioxide 13kg;
[0091] 6 kg of polymer emulsion, prepared in Preparation Example 5;
[0092] Defoaming agent 0.2kg;
[0093] Dispersant 0.5kg;
[0094] 30kg of water.
[0095] A method for preparing a water-based inorganic coating comprises the following steps: mixing a modified potassium silicate solution, heavy calcium carbonate, feldspar powder, titanium dioxide, polymer emulsion, defoamer, dispersant and water according to the weight required by the formula and stirring evenly to obtain the water-based inorganic coating.
[0096] Embodiment 2:
[0097] A water-based inorganic coating comprising the following components by weight:
[0098] 18 kg of modified potassium silicate solution, prepared in Preparation Example 2;
[0099] Heavy calcium carbonate 22kg;
[0100] Feldspar powder 4kg;
[0101] Titanium dioxide 8kg;
[0102] 3 kg of polymer emulsion, prepared in Preparation Example 6;
[0103] Defoaming agent 0.1kg;
[0104] Dispersant 0.2kg;
[0105] 20kg water.
[0106] A method for preparing a water-based inorganic coating comprises the following steps: mixing a modified potassium silicate solution, heavy calcium carbonate, feldspar powder, titanium dioxide, polymer emulsion, defoamer, dispersant and water according to the weight required by the formula and stirring evenly to obtain the water-based inorganic coating.
[0107] Embodiment 3:
[0108] A water-based inorganic coating comprising the following components by weight:
[0109] 20 kg of modified potassium silicate solution, prepared in Preparation Example 3;
[0110] Heavy calcium carbonate 25kg;
[0111] 5kg feldspar powder;
[0112] Titanium dioxide 10kg;
[0113] 4.5 kg of polymer emulsion, prepared in Preparation Example 7;
[0114] Defoaming agent 0.15kg;
[0115] Dispersant 0.3kg;
[0116] 25kg of water.
[0117] A method for preparing a water-based inorganic coating comprises the following steps: mixing a modified potassium silicate solution, heavy calcium carbonate, feldspar powder, titanium dioxide, polymer emulsion, defoamer, dispersant and water according to the weight required by the formula and stirring evenly to obtain the water-based inorganic coating.
[0118] Embodiment 4:
[0119] The only difference from Example 3 is that the modified potassium silicate solution is prepared using Preparation Example 4.
[0120] Embodiment 5:
[0121] The only difference from Example 3 is that in the first step of the preparation process of the modified potassium silicate solution, 0.1 kg of phytic acid is added.
[0122] Embodiment 6:
[0123] The only difference from Example 3 is that in the first step of the preparation process of the modified potassium silicate solution, 0.2 kg of phytic acid is added.
[0124] Embodiment 7:
[0125] The only difference from Example 6 is that 2 kg of hemp oil is also added to the water-based inorganic coating.
[0126] Embodiment 8:
[0127] The only difference from Example 6 is that 3 kg of hemp oil is also added to the water-based inorganic coating.
[0128] Embodiment 9:
[0129] The only difference from Example 8 is that the amount of polymer emulsion added is 6 kg.
[0130] Embodiment 10:
[0131] The only difference from Example 8 is that the polymer emulsion is a commercially available silicone acrylic emulsion.
[0132] Comparative Example 1:
[0133] The only difference from Example 3 is that the modified potassium silicate solution is replaced by a low modulus potassium silicate solution in equal mass.
[0134] Performance Test:
[0135] Referring to the method described in GB / T 6753.3-1986 "Test method for storage stability of coatings", the water-based inorganic coatings of Examples 1-10 and Comparative Example 1 were tested for storage stability. The storage temperatures were tested at 25°C and 5°C, respectively, and the number of months of storage without abnormalities was recorded. The results are shown in Table 1.
[0136] Referring to the water immersion test method described in GB / T 1733-1993 "Determination of water resistance of paint films", the water resistance of the waterborne inorganic coatings of Examples 1-10 and Comparative Example 1 was tested, and the results are shown in Table 1.
[0137] Referring to the method described in GB / T 1732-2020 “Determination of impact resistance of paint films”, the water-based inorganic coatings of Examples 1-10 and Comparative Example 1 were subjected to impact resistance tests, and the results are shown in Table 1.
[0138] Table 1 Water-based inorganic coating performance test results record
[0139]
[0140] It can be seen from Table 1 that the water-based inorganic coating of the present application has excellent storage stability, especially low-temperature storage stability, and has good water resistance and impact resistance, meeting the use requirements.
[0141] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A water-based inorganic coating, characterized in that: The composition comprises the following components in parts by weight: 18-24 parts of modified potassium silicate solution; Heavy calcium carbonate 22-30 parts; 4-6 parts of feldspar powder; 8-13 parts of titanium dioxide; 3-6 parts of polymer emulsion; Defoaming agent 0.1-0.2 parts; Dispersant 0.2-0.5 parts; 20-30 parts water; The preparation process of the modified potassium silicate solution is as follows: The first step is to mix 3-5 parts of silane coupling agent, 0.1-0.2 parts of acetic acid and 10-15 parts of water by weight, heat to 50-60° C., and react for 30-60 minutes to obtain a coupling agent solution; The second step is to mix 40-50 parts of low modulus potassium silicate solution and 15-20 parts of silica sol, continue stirring and heat to 55-60°C, keep warm for 40-60 minutes, add 2-3 parts of coupling agent solution and 15-20 parts of water, continue to keep warm for 2-3 hours, cool to room temperature, and discharge to obtain modified potassium silicate solution; The preparation process of the silane coupling agent is as follows: by weight, 10-13 parts of γ-glycidyloxypropyltrimethoxysilane, 15-17 parts of benzotriazole and 0.2-0.4 parts of Fe3O4 are mixed evenly, heated to 120-130°C, reacted for 45-60 minutes, cooled and discharged to obtain the silane coupling agent.
2. The water-based inorganic coating according to claim 1, characterized in that: The low modulus potassium silicate solution has a modulus of 2-2.5 and a mass concentration of 30-35 wt %.
3. The water-based inorganic coating according to claim 1, characterized in that: In the first step of the preparation process of the modified potassium silicate solution, 0.1-0.2 parts by weight of phytic acid is also added.
4. The water-based inorganic coating according to claim 1, characterized in that: By weight, 2-3 parts of hemp oil are also included.
5. The water-based inorganic coating according to claim 1, characterized in that: The preparation process of the polymer emulsion is as follows: The first step is to mix 20-25 parts of triethoxyvinylsilane, 0.6-0.9 parts of p-toluenesulfonic acid and 150-200 parts of tetrahydrofuran by weight under nitrogen protection, continue stirring and heat to 65-70° C., then add 30-40 parts of 4-fluoro-1-butanol, react for 3-5 hours, cool, filter, and distill under reduced pressure to obtain a fluorosilicone monomer; The second step is to mix 60-70 parts of butyl acrylate, 1.5-2 parts of OP-10, 0.3-0.5 parts of sodium bicarbonate and 300-400 parts of water under nitrogen protection, stir for 20-30 minutes, add 0.02-0.03 parts of potassium persulfate, heat to 80-85°C, react for 60-80 minutes, and obtain butyl acrylate emulsion; The third step is to mix the above fluorosilicone monomer with 20-30 parts of butyl acrylate, 40-50 parts of methyl methacrylate, 1.5-2 parts of OP-10, 0.3-0.5 parts of potassium persulfate and 500-600 parts of water, stir for 20-30 minutes, then add the above butyl acrylate emulsion, heat to 70-80°C, react for 3-4 hours and then discharge to obtain a polymer emulsion.
6. The water-based inorganic coating according to claim 5, characterized in that: The polymer emulsion accounts for more than 25wt% of the mass of the modified potassium silicate solution.
7. The water-based inorganic coating according to claim 1, characterized in that: The defoamer is a polyether defoamer.
8. The water-based inorganic coating according to claim 1, characterized in that: The dispersant is a non-ionic dispersant.
9. A method for preparing a water-based inorganic coating according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing modified potassium silicate solution, heavy calcium carbonate, feldspar powder, titanium dioxide, polymer emulsion, defoamer, dispersant and water according to the required weight parts of the formula and stirring evenly to obtain water-based inorganic coating.
Citation Information
Patent Citations
Silicate waterproof coating and preparation method thereof
CN118240406A